2012
DOI: 10.4049/jimmunol.1103040
|View full text |Cite
|
Sign up to set email alerts
|

Functional Changes in Myeloid-Derived Suppressor Cells (MDSCs) during Tumor Growth: FKBP51 Contributes to the Regulation of the Immunosuppressive Function of MDSCs

Abstract: Myeloid-derived suppressor cells (MDSCs) are increased by tumor-derived factors and suppress anti-tumor immunity. MDSCs obtained at a late time point after tumor injection had stronger suppressive activity than MDSCs obtained at an early time point, as measured by T cell proliferation assays. To find factors in MDSCs that change during tumor growth, we analyzed gene expression profiles from MDSCs at different time points after tumor injection. We found that immune response-related genes were downregulated but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
(83 reference statements)
4
37
0
Order By: Relevance
“…In support of this, inhibition of Tregs by monoclonal antibodies has been shown to decrease tumor development [134,135]. In addition, other regulatory cell populations such as MDSCs which accumulate in spleen, blood, tumors, and bone marrow of tumor-bearing mice and cancer patients [136,137] have been considered as important targets for therapeutic intervention [138]. MDSCs secrete IL-10 and TGF-␤ and enhance angiogenesis and metastasis by inducing Treg production [23,139].…”
Section: Cellular Targetsmentioning
confidence: 98%
“…In support of this, inhibition of Tregs by monoclonal antibodies has been shown to decrease tumor development [134,135]. In addition, other regulatory cell populations such as MDSCs which accumulate in spleen, blood, tumors, and bone marrow of tumor-bearing mice and cancer patients [136,137] have been considered as important targets for therapeutic intervention [138]. MDSCs secrete IL-10 and TGF-␤ and enhance angiogenesis and metastasis by inducing Treg production [23,139].…”
Section: Cellular Targetsmentioning
confidence: 98%
“…37 In contrast, NKT cells suppresses MDSC accumulation during viral infection, 29 and activated NKT cells can induce MDSC differentiation into DCs. 29,46,57,58 In expanded memory T cell cultures, an increased number of mouse CD49b C T cells or human CD161 C T cells reduced the suppressive effects of MDSCs, leading to enhanced IFNg production in response to tumor antigens. 45,58 Although these studies did not use markers that allow definitive identification of NKT cells, they are consistent with our findings that activated NKT cells rescued T cell proliferation from MDSC mediated suppression.…”
Section: Discussionmentioning
confidence: 99%
“…After prolonged contact with glioma cells microglia seem to lose their phagocytic properties. Moreover, it was reported that MDSCs associated with advanced stage disease show stronger suppressive properties than MDSCs occurring early in murine breast cancer models [224]. Down-regulation of transcription of immune response-related genes as well as an up-regulation of tumourpromoting genes in MDSCs was detected at a late time point of tumourigenesis.…”
Section: Dynamics Of the Glioma Cell-myeloid Immune Cell Interactionmentioning
confidence: 98%
“…Down-regulation of transcription of immune response-related genes as well as an up-regulation of tumourpromoting genes in MDSCs was detected at a late time point of tumourigenesis. In this study, FKBP51 -a cis-trans prolylisomerase that binds to the immunosuppressant FK506 and rapamycin -was identified to play an important role in the regulation of the suppressive functions of MDSCs [224].…”
Section: Dynamics Of the Glioma Cell-myeloid Immune Cell Interactionmentioning
confidence: 99%